Disturbed bone marrow adiposity in patients with Cushing’s syndrome and glucocorticoid- and postmenopausal- induced osteoporosis - Sørensen, Nina N.; Andreasen, Christina M.; Jensen, Pia R.; Hauge, Ellen M.; Bollerslev, Jens; Delaissé, Jean-Marie; Kassem, Moustapha; Jafari, Abbas; Diaz-delCastillo, Marta; Andersen, Thomas L. (Frontiers in Endocrinology, 2023)
Background: Skeletal stem/progenitor cells (SSPCs) in the bone marrow can differentiate into osteoblasts or adipocytes in response to microenvironmental signalling input, including hormonal signalling. Glucocorticoids (GC) are corticosteroid hormones that promote adipogenic differentiation and are endogenously increased in patients with Cushing´s syndrome (CS). Here, we investigate bone marrow adiposity changes in response to endogenous or exogenous GC increases. For that, we characterize bone biopsies from patients with CS and post-menopausal women with glucocorticoidinduced osteoporosis (GC-O), compared to age-matched controls, including postmenopausal osteoporotic patients (PM-O).Methods: Transiliac crest bone biopsies from CS patients and healthy controls, and from postmenopausal women with GC-O and matched controls were analysed; an additional cohort included biopsies from women with PM-O. Plastic-embedded biopsies were sectioned for histomorphometric characterization and quantification of adipocytes. The fraction of adipocyte area per tissue (Ad.Ar/T.Ar) and marrow area (Ad.Ar/Ma.Ar), mean adipocyte profile area (Ad.Pf.Ar) and adipocyte profile density (N.Ad.Pf/Ma.Ar) were determined and correlated to steroid levels.Furthermore, the spatial distribution of adipocytes in relation to trabecular bone was characterized and correlations between bone marrow adiposity and bone remodeling parameters investigated.Results: Biopsies from patients with CS and GC-O presented increased Ad.Ar/Ma.Ar, along with adipocyte hypertrophy and hyperplasia. In patients with CS, both Ad.Ar/Ma.Ar and Ad.Pf.Ar significantly correlated with serum cortisol levels. Spatial distribution analyses revealed that, in CS, the increase in Ad.Ar/Ma.Ar near to trabecular bone (<100 µm) was mediated by both adipocyte hypertrophy and hyperplasia, while N.Ad.Pf/Ma.Ar further into the marrow (>100 µm) remained unchanged. In contrast, patients with GC-O only presented increased Ad.Ar/Ma.Ar and mean Ad.Pf.Ar>100 µm from trabecular bone surface, highlighting the differential effect of increased endogenous steroid accumulation. Finally, the Ad.Ar/Ma.Ar and Ad.Ar/T.Ar correlated with the canopy coverage above remodeling events.Increased cortisol production in patients with CS induces increased bone marrow adiposity, primarily mediated by adipocyte hypertrophy. This adiposity is particularly evident near trabecular bone surfaces, where hyperplasia also occurs. The differential pattern of adiposity in 4 This is a provisional file, not the final typeset article patients with CS and GC-O highlights that bone marrow adipocytes and their progenitors may respond differently in these two GC-mediated bone diseases.